Investigation of the structural interaction between the wing and body of a class of simple remotely piloted aircraft - Ahn, D. M. (Cranfield University, 1982)
Effects of various wing-body interaction design parameter variations on the structural behaviour of a small RPV have been investigated using the finite element method on an adhoc basis rather than a classical analytic approach. The method in use is based on the substructuring displacement method considering the body and the wing as two major substructures. The elastic coupling effect of wing stiffness on the body structural behaviour also examined. By comparing classical analysis methods to the present. investigation, comments are made upon the use of those methods in the design analysis of the RPV class of structure. From the calculated results, general guidelines on the structural wing-body interaction analysis or design of this class of vehicle have been proposed. A set of finite element programs have been developed for the present investigation, and relevant finite elements based on the displacement assumption have been formulated.